2020
DOI: 10.1515/nanoph-2020-0401
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-sensitive photodetectors based on three-dimensional molybdenum disulfide (MoS2) field-effect transistors

Abstract: The molybdenum disulfide (MoS2)-based photodetectors are facing two challenges: the insensitivity to polarized light and the low photoresponsivity. Herein, three-dimensional (3D) field-effect transistors (FETs) based on monolayer MoS2 were fabricated by applying a self–rolled-up technique. The unique microtubular structure makes 3D MoS2 FETs become polarization sensitive. Moreover, the microtubular structure not only offers a natural resonant microcavity to enhance the optical field inside but also increases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…Subsequently, the enhancement of optical absorption can induce an increase in the number of photo-generated carriers, resulting in a rise in the photocurrent of the rolledup photodetector. Deng et al [107] reported a self-rolled up 3D MoS 2 photodetector. This distinct 3D tubular structure functions as an optical resonator and enables the 3D MoS 2 field-effect transistor (FET) to detect linear polarized light in addition to enhanced photodetection efficiency.…”
Section: D-structured Photodetectormentioning
confidence: 99%
“…Subsequently, the enhancement of optical absorption can induce an increase in the number of photo-generated carriers, resulting in a rise in the photocurrent of the rolledup photodetector. Deng et al [107] reported a self-rolled up 3D MoS 2 photodetector. This distinct 3D tubular structure functions as an optical resonator and enables the 3D MoS 2 field-effect transistor (FET) to detect linear polarized light in addition to enhanced photodetection efficiency.…”
Section: D-structured Photodetectormentioning
confidence: 99%
“…In the 2D case, graphene along with patterned contacts, supported on strained SiN x layer pairs and released by etching of a sacrificial Al film, is rolled up into a cylindrical FET photodetector. A similar fabrication method has been reported for other 2D crystals, including MoS 2 ( Deng et al., 2020 ), while alternative approaches use evaporated bimetallic strips both for rolling and as device contacts ( Zhou et al., 2019 ). The cylindrical graphene FET photodetectors demonstrated efficient photodetection in the UV, visible, mid-infrared, and terahertz (THz) regions, while MoS 2 scrolls showed polarization-dependent photocurrent, where symmetry breaking results from the cylindrical geometry of the detector.…”
Section: D Goes 3dmentioning
confidence: 99%
“… 13 Therefore, MoS 2 has recently attracted more and more research attention in high-performance photodetectors. 7 , 14 …”
Section: Introductionmentioning
confidence: 99%